Hierarchically biomimetic scaffold of a collagen–mesoporous bioactive glass nanofiber composite for bone tissue engineering. (25th March 2015) - Hsu, Fu-Yin; Lu, Meng-Ru; Weng, Ru-Chun; Lin, Hsiu-Mei
Abstract: Mesoporous bioactive glass nanofibers (MBGNFs) were prepared by a sol–gel/electrospinning technique. Subsequently, a collagen–MBGNF (CM) composite scaffold that simultaneously possessed a macroporous structure and collagen nanofibers was fabricated by a gelation and freeze-drying process. Additionally, immersing the CM scaffold in a simulated body fluid resulted in the formation of bone-like apatite minerals on the surface. The CM scaffold provided a suitable environment for attachment to the cytoskeleton. Based on the measured alkaline phosphatase activity and protein expression levels of osteocalcin and bone sialoprotein, the CM scaffold promoted the differentiation and mineralization of MG63 osteoblast-like cells. In addition, the bone regeneration ability of the CM scaffold was examined using a rat calvarial defect model in vivo . The results revealed that CM is biodegradable and could promote bone regeneration. Therefore, a CM composite scaffold is a potential bone graft for bone tissue engineering applications.